Experimental observation of triple correlations in fluids - Sushko, M.Ya. (Condensed Matter Physics, 2013)
We present arguments for the hypothesis that under some conditions, triple correlations of density fluctuations in fluids can be detected experimentally by the method of molecular spectroscopy. These correlations manifest themselves in the form of so-called 1.5-(or sesquialteral) scattering. The latter is of most significance in the pre-asymptotic vicinity of the critical point and can be registered along certain thermodynamic paths. Its presence in the overall scattering pattern is demonstrated by our processing available experimental data for the depolarization factor. Some consequences of these results are discussed. Наведено аргументи на користь гiпотези, що при певних умовах методом молекулярної спектроскопiї можна зареєструвати потрiйнi кореляцiї флуктуацiй густини в рiдинах. Цi кореляцiї проявляють себе у виглядi так званого 1.5- (тобто пiвторакратного) розсiяння, яке є найбiльш суттєвим в передасимптотичнiй областi критичної точки та може бути зареєстроване вздовж певних термодинамiчних шляхiв. Його присутнiсть у загальнiй картинi розсiяння демонструється результатами обробки вiдомих експериментальних даних для коефiцiєнта деполяризацiї. Обговорено деякi наслiдки цих результатiв.